Concepts of Translation of Takwil, Tafsir, and Hermeneutics in the Science of the Al-Qur’an - Arrasyid Arrasyid; Toni Markos; Siti Aqilah (Jurnal Kawakib, 2023)
The study of the Quran encompasses a multitude of significant concepts pertaining to the interpretation and comprehension of its text. This qualitative research employs the method of descriptive analysis to expound upon the process of translating the Quranic text from its original Arabic form into other languages. The act of translation is of paramount importance due to the Quran's initial revelation in Arabic, rendering comprehension of its content and message inaccessible to non-Arabic speakers without the aid of translation. The concepts of takwil and tafsir serve to facilitate the interpretation of the Quranic meaning, with the former referring to a meaning that is not explicitly stated in the text, and the latter involving a more in-depth interpretation of the Quranic text, considering its historical and cultural context. Hermeneutics, a comprehensive and systematic methodology of text interpretation, is instrumental in the science of the Quran, given the intricacy and multiplicity of meanings within its text, necessitating scrupulous and diligent understanding.